2005
DOI: 10.1900/rds.2005.2.221
|View full text |Cite
|
Sign up to set email alerts
|

Shell-Less Chick Embryo Culture as an Alternative in vitro Model to Investigate Glucose-Induced Malformations in Mammalian Embryos

Abstract: ■ AbstractWe have developed a simple shell-less chick embryo culture system to study glucose-induced malformations. This system involves the culturing of chick embryos from the second day to the fifth day of incubation, with associated yolk and thick and thin albumen outside the egg shell. The system allows the observation of embryonic development of chicks in a glass bowl. Developing embryos at 24 h, 48 h and 72 h incubation, corresponding to the Hamberger Hamilton (HH) stages from 7 to 21, were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 38 publications
2
28
0
Order By: Relevance
“…Hence, it is unlikely that caudal regression was mediated by vascular disruption at least in the present chick model. Caudal regression syndrome-like anomalies has been reported to develop in glucose-treated and insulin-treated chick embryos (33,34). In both studies, the mortality and morbidity were developmental stage dependent.…”
Section: Discussionmentioning
confidence: 92%
“…Hence, it is unlikely that caudal regression was mediated by vascular disruption at least in the present chick model. Caudal regression syndrome-like anomalies has been reported to develop in glucose-treated and insulin-treated chick embryos (33,34). In both studies, the mortality and morbidity were developmental stage dependent.…”
Section: Discussionmentioning
confidence: 92%
“…Work from our lab has shown that isolated chick islets are suitable for screening of hypoglycemic agents and for islet banking (Figure 1) [12,13]. Our work has also revealed that the shell-less chick embryo culture system can be used for studying glucose-induced malformations similar to those observed in mammalian embryos [14].…”
Section: Introductionmentioning
confidence: 80%
“…Different diabetic malformations of mammalian gestational diabetes, such as embryonic dismorphogenesis, rotational defects, cardiovascular abnormalities, macrosomia, macrocephaly, and retarded growth could be observed using this system. This study indicated that the developing chick embryo provides an excellent alternative model system to mammalian embryo models for the study of glucose-induced malformations [14]. The shell-less chick embryo culture system can also be employed in biomedical research for exploring the effects of angiogenic agents, vitamins, antibiotics, viruses, and carcinogenic agents.…”
Section: Chick Embryo As a Model For Depicting Glucose-induced Malformentioning
confidence: 95%
See 1 more Smart Citation
“…enabled study of organogenesis, angiogenesis, hematology, and the physiological function of the cardiovascular system in bird embryos just a few days old (Burggren et al, 2004;Datar and Bhonde, 2005;Khorrami et al, 2008;Branum et al, 2013). Figure 6 illustrates the process of growing embryos in shell-less culture as well as physiological information that can be derived from them.…”
Section: Organic Toxicants As Developmental Disruptorsmentioning
confidence: 99%